Beyond therapy: bringing social work back to human services reform - Jacobson, Wendy B. (2001)
Based on field interviews in a Chicago community development corporation and settlement houses in New York City and St. Louis, as well as interviews with leading social services innovators and social work educators, this article explores the intersection of current social work practice and human services innovation. The article offers a rationale and a blueprint for a reorientation of social work's "helping relationship," reviews a number of promising innovations and strategies that may help the profession make this reorientation operational, and explores forces restraining as well as driving such change. - Reproduced
Keywords: Social work